2014
DOI: 10.2147/ndt.s69681
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic regional brain spontaneous activity and subjective sleep quality in patients with chronic primary insomnia: a resting-state fMRI study

Abstract: Study objectiveTo prospectively explore the underlying regional homogeneity (ReHo) brain-activity deficit in patients with chronic primary insomnia (PCPIs) and its relationship with clinical features.DesignThe ReHo method and Statistical Parametric Mapping 8 software were used to evaluate whether resting-state localized brain activity was modulated between PCPIs and good sleepers (GSs), and correlation analysis between altered regional brain areas and clinical features was calculated.Patients and participantsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 63 publications
6
121
0
1
Order By: Relevance
“…48 Joo et al found that the PCPIs showed significant reduction of gray matter concentrations in the dorsolateral prefrontal cortices compared with the GSs. 7 Our previous study also found the PCPI-Ms showed lower regional homogeneity in the dorsolateral prefrontal cortex compared with the GS-Ms. 23 In support of these findings, in the present study we found that the PCPI-Fs showed lower ALFF in the left dorsolateral prefrontal cortex compared with the GS-Fs. These findings suggest that the attentional and cognitive dysfunction may contribute to the impaired dorsolateral prefrontal cortex.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…48 Joo et al found that the PCPIs showed significant reduction of gray matter concentrations in the dorsolateral prefrontal cortices compared with the GSs. 7 Our previous study also found the PCPI-Ms showed lower regional homogeneity in the dorsolateral prefrontal cortex compared with the GS-Ms. 23 In support of these findings, in the present study we found that the PCPI-Fs showed lower ALFF in the left dorsolateral prefrontal cortex compared with the GS-Fs. These findings suggest that the attentional and cognitive dysfunction may contribute to the impaired dorsolateral prefrontal cortex.…”
Section: Discussionsupporting
confidence: 87%
“…7 Altena et al found a smaller gray matter volume in the left orbitofrontal cortex in the PCPIs compared with the GSs. 45 Our previous regional homogeneity study found that both the PCPI-Fs and the PCPI-Ms showed lower regional homogeneity in the VMPFC, 23 and our previous functional connectivity study found that the PCPIs showed significant decreased functional connectivity between the MPFC and the right MTL, and between the left MTL and the left inferior parietal cortices using the seed-based region-to-region functional connectivity method. 12 In support of these findings, in the present study we found that the PCPI-Fs showed higher ALFF in the bilateral MTL and lower ALFF in the bilateral VMPFC and right MTL compared with the GS-Fs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations